Labour unionism in the financial services sector : fighting for rights and representation - Gall, Gregor (Ashgate, 2008)
This book examines, in wider historical terms, the development of unionisation and collectivism within the financial services sector.
Keywords: Financial services industry -- Employees -- Labor unions -- Great Britain.; Labor unions -- Great Britain.; Services financiers -- Personnel -- Syndicats -- Grande-Bretagne.; Syndicats -- Grande-Bretagne.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Labor unions; Great Britain; Computer network resources.